The Nottingham Fatigue after Stroke (NotFAST) study: factors associated with severity of fatigue in stroke patients without depression. (October 2017) - Drummond, Avril; Hawkins, Louise; Sprigg, Nikola; Ward, Nick S; Mistri, Amit; Tyrrell, Pippa; Mead, Gillian E; Worthington, Esme; Lincoln, Nadina B
Objective: To identify factors associated with post-stroke fatigue in a sample of stroke survivors without depression. Design: Cross-sectional cohort study. Setting: Recruitment was from four stroke units in the UK. Subjects: Participants were assessed within four to six weeks of first stroke; those with high levels of depressive symptoms (score ⩾7 Brief Assessment Schedule Depression Cards) were excluded. Main measures: Participants were assessed after stroke on the Fatigue Severity Scale of the Fatigue Assessment Inventory, the Rivermead Mobility Index, Nottingham Extended Activities of Daily Living scale, Beck Anxiety Index, Sleep Hygiene Index, 6m walk test, and measures of cognitive ability. Results: Of the 371 participants recruited, 103 were excluded and 268 were assessed. Of the latter, the mean age was 67.7 years (SD 13.5) and 168 (63%) were men. The National Institutes of Health Stroke Scale mean score was 4.96 (SD 4.12). Post-stroke fatigue was reported by 115 (43%) of participants, with 71 (62%) reporting this to be a new symptom since their stroke. Multivariate analysis using the Fatigue Severity Scale as the outcome variable found pre-stroke fatigue, having a spouse/partner, lower Rivermead Mobility Index score, and higher scores on both the Brief Assessment Schedule Depression Cards and Beck Anxiety Index were independently associated with post-stroke fatigue, accounting for approximately 47% of the variance in Fatigue Severity Scale scores. Conclusions: Pre-stroke fatigue, lower mood, and poorer mobility were associated with post-stroke fatigue.